Ultrasound-assisted modification of oat protein isolates: Structural and functional enhancements - Hamad Rafique; Pai Peng; Xinzhong Hu; Kanza Saeed; Muhammad Zubair Khalid; Waseem Khalid; Sonia Morya; Tawfiq Alsulami; Robert Mugabi; Gulzar Ahmad Nayik (Ultrasonics Sonochemistry)
Escalating global protein demand necessitates the commercialization of protein rich products. Oat is a promising high-quality protein source but it requires structural and functional modifications to diversify its application. The current investigation was focused on the impact of different powers of ultrasonic waves (200, 400, and 600 W) on structural and functional characteristics of oat protein isolates to improve its techno-functional properties. Higher strength ultrasound waves generated flat sheet structures which were observed while analyzing microstructure of oat protein isolate (OPI). However, non-significant variation in molecular weight distribution were observed in different treatments. At 600 W power of ultrasonic waves the protein fragments show local accumulation, increased α-helix content. Due to uncoiling of protein structure decrease in β-sheets and β-turns was also observed at 600 W. Protein turbidity decreased significantly under low power ultrasonic treatment (200 W) which significantly increased at higher power. Moderate ultrasonic treatment (400 W) promoted protein dissolution, and maintained a good balance between β-sheets (71.04 ± 0.08), α-helix (16.27 ± 0.02) and β-turns (12.68 ± 0.03), exhibiting optimized flexibility and structural integrity. Whereas, higher strength (600 W) significantly destroyed protein structure. The amino acid content decreased significantly with increasing ultrasonic power. The thermal characteristics of OPI remained unaffected after ultrasound treatment. In conclusion, modifications of secondary and tertiary structure induced by moderate ultrasonic treatment (400 W) improved functional properties of OPI. The 400 W treatment resulted in highest essential amino acid content (EAA) i.e., 22.75 ± 0.82 mg/100 mg and total amino acid content (TAA) i.e., 64.94 ± 2.7 mg/100 mg, which are significantly higher than WHO and FAO standards, suggesting best total and essential amino acid production in comparison to other treatments.